Passivation of Cu-Rh Alloys - Xie, Yusi; Chatterjee, Swarnendu; Liu, Ling-Zhi; Jin, Hai-Jun; Sieradzki, Karl (Journal of the Electrochemical Society, 2021)
Historically, there have been two general approaches for understanding alloy passivation behavior. One involves study of the composition and crystal structure of the passive film and the other is concerned with how the composition and structure of the metallic alloy dictates the formation of the film. Herein we describe a recently developed theory based on a conjecture of Sieradzki and Newman connected to percolation theory and use the theory to model the passivation behavior of a series of Cu-Rh alloys. Our results are in quantitative agreement with the predictions of this theory. We discuss how the theory elucidates the important role of short-range order in understanding how composition affects the details of the passivation process.